THE STRATEGIES OVERCOME MISPRONUNCIATION IN DAILY VOCABULARY AT EFL STUDENT - Wizarotul Maghfiroh; Salza Febi Putri Melati (2025)
Pronunciation is a crucial skill to gain perfect English skill. Learners within proper pronunciation will be able to comprehend and communicate effectively. Therefore, much of the learner still has difficulty using correct pronunciation for several reasons and there will be several effects related to lack of pronunciation. Thus, identifying how to overcome error of mispronunciation is crucial. The purpose of this study was to discover the strategies of mispronunciation, especially within common or daily words. This study uses a qualitative approach within thematic analysis. The data gathered from a structured interview by 15 learners to unlock their pronunciation for several common words and 5 learners to gain their problem with pronunciation. Thus, the research found that most of the learners still lack the pronunciation of common words in the rage 41,26%. In addition, the research unlocked the strategies to maximalize well-formed of pronunciation such as combine repetition, listening, digital support, and confidence-building. These methods reflect a growth mindset, where mistakes are seen as a normal and valuable part of learning.